Inhibition kinetics, molecular docking, and stability studies of the effect of papain-generated peptides from palm kernel cake proteins on angiotensin-converting enzyme (ACE) - Zarei, Mohammad (Elsevier, 2022)
Three novel peptide sequences YGIKVGYAIP, GGIF, and GIFE from papain-generated protein hydrolysate of palm kernel cake proteins were used for stability study against ACE, ACE-inhibition kinetics, and molecular docking studies. Results showed that peptide YGIKVGYAIP was degraded, and its ACE-inhibitory activity decreased after 3 h pre-incubation with ACE, while peptides GGIF and GIFE were resistant. However, although the ACE-inhibitory activity of GIFE increased during this time, the ACE inhibitory activity of GGIF decreased after pre-incubation with ACE, indicating that peptide. YGIKVGYAIP and GGIF are substrate-type, whereas GIFE is a true-inhibitor type. Peptide YGIKVGYAIP showed the lowest Ki (0.054 mM) in the inhibition kinetics study compared to GGIF and GIFE, with Ki of 1.27 m M and 18 mM, respectively. In addition, YGIKVGYAIP revealed the lowest Km and Vmax and higher CE in different peptide concentrations, implying that the enzyme catalysis decreased, and peptides had some binding affinity to the enzyme in lower concentrations, which led to reduced catalytic ability. Furthermore, YGIKVGYAIP showed the lowest docking score of −14.733 and 21 interactions with tACE, while GGIF revealed the higher docking score of −8.006 with 15 interactions with tACE.